2019
DOI: 10.1007/978-3-030-32497-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Modern TRIZ Based on Practical Results in New Product Development

Abstract: Today's innovation processes used in industry are generally inefficient: various sources indicate that only one out of three-thousand, raw ideas yield a commercial product. Fortunately, most of the ideas are quickly rejected before much time and money are spent on their development. Still, approximately 300 of the raw ideas are normally selected for further investigation and development, which results in launching around 125 small pilot projects and in other time and money-consuming activitiesall for the sake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Based on the experimental analysis, Hernandez et al concluded that TRIZ improves the ideation effectiveness compared to a control group using ad hoc ideation methods (Hernandez et al , 2013). Research results also showed that using TRIZ has improved the efficiency of the new product development process from about 5–12 times (Abramov et al , 2019). Based on Poppe and Gras (Poppe and Gras, 2002), TRIZ is accepted by Western companies because it could enable them to rapidly innovate a product and increase their competitiveness in the present competitive market.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the experimental analysis, Hernandez et al concluded that TRIZ improves the ideation effectiveness compared to a control group using ad hoc ideation methods (Hernandez et al , 2013). Research results also showed that using TRIZ has improved the efficiency of the new product development process from about 5–12 times (Abramov et al , 2019). Based on Poppe and Gras (Poppe and Gras, 2002), TRIZ is accepted by Western companies because it could enable them to rapidly innovate a product and increase their competitiveness in the present competitive market.…”
Section: Resultsmentioning
confidence: 99%